COMPARISON OF AEROTECHNICS DEVISE MAINTENANCE EFFICIENCY WHICH ARE EXPLOITED WITH THE TECHNICAL CONDITION FOR DIFFUSION-MONOTONIC AND DIFFUSION-NONMONOTONIC FAILURE DISTRIBUTION MODELS - Volodymyr I. Mirnenko; Serhii O. Pustovyi; Petro M. Yablonskyi; Oleksandr V. Avramenko (Sučasnì Informacìjnì Tehnologìï u Sferì Bezpeki ta Oboroni)
For the model of aerotechnics wares maintenance, which are exploited on the technical state, analytical dependences of the technical use (Кtu) coefficient from the exploitation parameters for diffusion-monotonic (DM) and diffusion-nonmonotonic (DN) failures distributions are set. Comparative descriptions of Кtu from periodicity and duration of realization of maintenance, authenticity of equipment control, probability of signals receipt about a failure, coefficients of scale and shape of DM and DN distributions, duration of complete renewal of ware are shown. Existence of an optimal frequency of maintenance work, which provides a maximum value is shown. For the description of mathematical model a semi-Markov stochastic process is used in his classic understanding. Basic results obtained by using the numerical method of calculation.